Empirical evidence on the aggregate effects of anticipated and unanticipated US tax policy shocks - Karel Mertens; Morten O. Ravn (National Bank of Belgium, 2009)
The authors provide empirical evidence on the dynamic effects of tax liability changes in the United States. We distinguish between surprise and anticipated tax changes using a timing convention. We document that pre-announced but not yet implemented tax cuts give rise to contractions in output, investment and hours worked, while real wages increase. In contrast, there are no significant anticipation effects on aggregate consumption. Implemented tax cuts, regardless of their timing, have expansionary and persistent effects on output, consumption, investment, hours worked and real wages. The findings are shown to be very robust. We argue that tax shocks are empirically important impulses to the US business cycle and that anticipation effects have been significant over several business cycle episodes
Keywords: E20; E32; E62; H30; 330; fiscal policy shocks; tax liabilities; anticipation effects; business cycles; Steuerpolitik; Steuersenkung; Ankündigungseffekt; Bruttoinlandsprodukt; Privater Konsum; Lohnniveau; Konjunktur; USA